CLOUD RESOURCES AND SERVICES FOR TRAINING OF FUTURE SPECIALIST OF INFORMATION TECHNOLOGIES: SELECTION CRITERIA, CASE STUDIES - A. Gurzhii; O. Glazunova; T. Voloshyna; V. Korolchuk; О. Yakobchuk (Kherson State University, 2019)
The article presents the criteria and indicators for the selection of cloud resources and services for the training of future IT professionals. The cloud resources and services that are expedient to use in the process of training future IT professionals to provide them with training materials, services for practical tasks, tools for self-control and reflection are analyzed. Resources and services that were considered: academic resources and massive open online courses (MOOCs), platforms and automated programming systems, online programming labs, services and resources for teamwork, software development platforms, tools for management and modeling, professional community. In this reserch, a comparative characteristic of selected cloud resources and services based on certain criteria and indicators is given. In the expert evaluation of the identified criteria were involved 23 experts, who are scientific and pedagogical workers and have practical experience in training future specialists in the subject area 12 "Information Technologies" and specialties "Computer Science", "Software Engineering" and "Computer Engineering". At various stages of the research, between 58 and 109 students were involved in the pedagogical experiment. As a result of the research, the classification of cloud resources and services for the training of future IT specialists are justified, the educational and methodological selection criteria for each type of resources and services and the weight of each criterion are used using the expert method are defined. Examples and results of the use of certain cloud resources and services in the process of training future IT specialists are given.